Evaluation of individualized management of children with ECC after treatment under dental general anesthesia via a virtual dental home intervention: a quasi-experimental study - Dai, Lina; Wu, Tingting; Zhang, Xinjing; Ye, Yujia; Zhou, Leijiang; Hu, Yun (Frontiers in Oral Health, 2025)
Introduction/objectivesThe recurrence rate is high in children with early childhood caries (ECC) after treatment under dental general anesthesia (DGA). The purpose of this study was to evaluate the effectiveness of a virtual dental home (VDH) intervention compared to a routine intervention in the management of children with ECC following treatment under DGA, focusing on enhancing parental oral health awareness.MethodsIn total, 35 child–caregiver couples presenting for treatment under DGA were randomly assigned to two groups: 19 couples in the VDH intervention group and 16 couples in the routine intervention group. The children's pre- and post-intervention number of decayed, missing, or filled teeth and caries risk assessment (CRA) were recorded during oral examinations. The participants' demographics, pre- and post-intervention Early Childhood Oral Health Impact Scale (ECOHIS) scores, the children's oral health behavior scores, and the parents' knowledge, attitudes, and practices (KAP) scores related to their children's oral health were collected through questionnaires. The length of the intervention was 2 years.ResultsAt baseline, no significant differences existed in demographic characteristics, CRA distribution, ECOHIS scores, the children's oral health behavior scores, or the parents' KAP scores related to their children's oral health between the two groups. At the 2-year follow-up, the ECOHIS scores significantly decreased in both groups. The mean parents' KAP and children's oral health behavior scores significantly improved in both groups, with a greater increase in the VDH intervention group. The children's CRA distribution changed significantly in the VDH intervention group compared to the routine intervention group. The caries-free rate was 47.37% in the VDH intervention group compared to 68.75% in the routine intervention group.ConclusionsThe VDH intervention significantly outperformed the routine intervention method in ECC prevention and management after treatment under DGA by increasing parental oral health awareness.Clinical perspectivesThis study aimed to evaluate the effectiveness of VDH intervention in preventing caries recurrence after ECC treatment under DGA. The results of this study showed that the VDH intervention, using a digital platform, was more effective in the management of ECC after treatment under DGA than the routine intervention method. These findings provide evidence for a shift toward technology-assisted models and artificial intelligence should be incorporated into the management of ECC in the future.